2019
DOI: 10.1111/jopr.13124
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effect of Glass Fiber and Nano‐Filler Addition on Denture Repair Strength

Abstract: Purpose To evaluate and compare the effects of glass fiber (GF), Zirconium oxide nanoparticles (nano‐ZrO2), and silicon dioxide nanoparticles (nano‐SiO2) addition on the flexural strength and impact strength of repaired denture base material. Materials and Methods Heat‐polymerized acrylic resin specimens were fabricated. All specimens were sectioned centrally and beveled creating 2.5 mm repair gap except for 10 controls. Specimen grouping (n = 10/group) was done according to filler concentration of 0%, 0.25%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 40 publications
1
49
0
Order By: Relevance
“…Various factors were of significance during the process of incorporating filler into PMMA: The distribution of the polymer matrix, the shape and size of the filler, and the level of bonding between the filler and the matrix [ 10 , 26 , 41 ]. The filler needs to be small enough to produce a homogenous mixtures and can penetrate between the linear macromolecule chains, thereby restricting their movement [ 9 , 42 ]. Previous studies have concluded that the percentage filler should be sufficiently low to ensure the fillers are embedded in the resin [ 15 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various factors were of significance during the process of incorporating filler into PMMA: The distribution of the polymer matrix, the shape and size of the filler, and the level of bonding between the filler and the matrix [ 10 , 26 , 41 ]. The filler needs to be small enough to produce a homogenous mixtures and can penetrate between the linear macromolecule chains, thereby restricting their movement [ 9 , 42 ]. Previous studies have concluded that the percentage filler should be sufficiently low to ensure the fillers are embedded in the resin [ 15 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of 1.5 wt.% and 5 wt.% ZrO 2 into PMMA also increased the flexural strength of the material; however, the difference was not statistically significant. Thus our proposal was that homogenized blending of fillers into a PMMA matrix might improve the strength of the material [ 11 , 42 ]. However, we observed that the higher ratios of particles led to appearances of clustering, which form spaces.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, PMMA absorbs water, which may compromise its physical and mechanical properties while in use [ 63 , 64 ] and make it vulnerable to failure under cyclic loading [ 65 ]. Currently, a number of researchers are focused on mechanical reinforcement [ 30 , 38 , 51 , 53 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ] and chemical modification [ 53 , 75 , 76 ] of PMMA to overcome its drawbacks and improve its properties, which have been reviewed in this article. In order to better understand and interpret these recent modifications, it is important to understand the chemistry, types, and properties of PMMA materials.…”
Section: Historical Background and Developmentmentioning
confidence: 99%
“…The nonuniformity of both components when mixing can lead to a decrease in material strength and bacterial invasion, which can decrease biocompatibility [ 6 ]. To overcome the shortcomings of PMMA, such as the inadequate mechanical properties and bacterial invasion, the material composition has been changed, and various reinforcing materials have been added [ 7 , 8 ]. However, because the conventional complete denture manufacturing method is complicated, the degree of perfection of the denture may differ depending on the experience and skill of the dentist or dental technician.…”
Section: Introductionmentioning
confidence: 99%